Picocyanobacteria Community and Cyanophage Infection Responses to Nutrient Enrichment in a Mesocosms Experiment in Oligotrophic Waters - Coello-Camba, Alexandra; Diaz-Rua, Ruben; Duarte, Carlos M.; Irigoien, Xabier; Pearman, John K.; Alam, Intikhab S.; Agusti, Susana (Frontiers in Microbiology, 2020)
Prochlorococcus and Synechococcus are pico-sized cyanobacteria that play a fundamental role in oceanic primary production, being particularly important in warm, nutrient-poor waters. Their potential response to nutrient enrichment is expected to be contrasting and to differ from larger phytoplankton species. Here, we used a metagenomic approach to characterize the responses to nutrient enrichment in the community of picocyanobacteria and to analyze the cyanophage response during a mesocosms experiment in the oligotrophic Red Sea. Natural picoplankton community was dominated by Synechococcus clade II, with marginal presence of Prochlorococcus (0.3% bacterial reads). Increased nutrient input triggered a fast Synechococcus bloom, with clade II being the dominant, with no response of Prochlorococcus growth. The largest bloom developed in the mesocosms receiving a single initial input of nutrients, instead of daily additions. The relative abundances of cyanophage sequences in cellular metagenomes increased during the experiment from 12.6% of total virus reads up to 40% in the treatment with the largest Synechococcus bloom. The subsequent collapse of the bloom pointed to a cyanophage infection on Synechococcus that reduced its competitive capacity, and was then followed by a diatom bloom. The cyanophage attack appears to have preferentially affected the most abundant Synechococcus clade II, increasing the evenness within the host population. Our results highlight the relevance of host-phage interactions on determining population dynamics and diversity of Synechococcus populations.